Uneven regional distribution of FDI in China and Guangdong's experience - Lan, Yisheng (Business in Asia and the Pacific working paper series, 1998)
Guangdong Province in southern China has attracted the largest amount of foreign investment since the economy was opened in 1979. Its advantages of being economically integrated with Hong Kong, having close ties with Overseas Chinese, and having better infrastructure and more skilled labour have been instrumental in its acendancy to top position amony the eastern provinces. Moreover, it has enjoyed preferential development status under China's Coastal Development Strategy. However, recent governmental rulings have designated equal opportunities for investment of all coastal and inland regions, hence dealing a blow on Guangdong's leadership position. This paper argues that the province's fundamental strengths can overcome this setback and that it will regain its primacy in the high-technology industrial sector.